2019
DOI: 10.1097/bpo.0000000000001451
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Proximal Femoral Varus Osteotomy Shorten the Duration of Fragmentation in Perthes Disease? Lessons From a Prospective Multicenter Cohort

Abstract: Background: The prognosis of Legg-Calvé-Perthes disease (LCPD) is dependent upon several factors, with the length and severity of the fragmentation stage among the most important. Previous retrospectively collected data from a single center have suggested that early proximal femoral varus osteotomy (PFO) may shorten the length of fragmentation and allow 34% of patients to bypass fragmentation altogether resulting in less femoral head deformity. The purpose of this study was to validate these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 30 publications
2
38
0
2
Order By: Relevance
“…One of the major shortcomings of this study is the small sample size, despite the fact that data collection extended over five years and it is likely that the differences in variables between the groups did not reach statistical significance on account of this. Though we could have included data of a larger number of children from the multi-centric database used in the study of Sankar et al 10 we opted not to do so. The reason for restricting the subjects to a single centre was because we felt it was important to have exactly the same treatment and the same post-operative protocol for all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major shortcomings of this study is the small sample size, despite the fact that data collection extended over five years and it is likely that the differences in variables between the groups did not reach statistical significance on account of this. Though we could have included data of a larger number of children from the multi-centric database used in the study of Sankar et al 10 we opted not to do so. The reason for restricting the subjects to a single centre was because we felt it was important to have exactly the same treatment and the same post-operative protocol for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Though these observations need further scrutiny, little new information regarding the phenomenon of bypassing fragmentation has appeared in the recent literature. 10 A very recent study 10 addressed the frequency of this phenomenon and concluded by stating that 'a more rigorous definition of what constitutes bypass is warranted'. This prompted us to undertake this prospective study to look more closely at the patterns of evolution of LCPD following containment surgery in stage Ia or Ib of the disease by a proximal femoral varus osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Second, because of the retrospective nature of the study, the intervals between serial radiographs were not standardized, probably leading to a greater overestimation of the actual stage duration than other prospective studies. 8,9 All school-aged patients, however, were examined every long holiday twice or 3 times a year until skeletal maturity, and patients and their parents were usually requested to visit 1 or 2 more times during the school day until implant removal. This examination schedule corresponds to 3 or 4-month intervals during the active stage of the disease and afterward at least 6 months intervals, being comparable with that of other prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is uncertain whether the phenomenon denotes complete bypass only or both complete and incomplete bypass. More recently, one prospective multicenter study, consisting of 46 patients, demonstrated that complete or incomplete bypass was observed in 2% or 17% of patients, respectively, who had been treated during the avascular necrosis stage 8. According to another prospective study, which classified epiphyseal fragmentation into 4 patterns, of 25 patients who received early FVO, complete bypassing was observed in 12%, and abortive fragmentation was done in 24% 9.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to show the long-term follow-up prognostic value of an advanced imaging method classification system applied in the initial stage of LCPD. Previous bone scan investigations showed the short-term correlation of the revascularization patterns with several radiographic classifications and outcome measures, but no long-term follow up study was further published [22,[31][32][33][34]. Advanced MRI techniques still lack long-term followup studies.…”
Section: Radiographic Classifications Have Been Developed In Anmentioning
confidence: 99%